PENGARUH PENAMBAHAN ISOLAT PROTEIN KEDELAI TERHADAP KARAKTERISTIK KAMABOKO IKAN BARRAMUNDI (Lates calcalifer) - Ilma, Praniti Radya Andana; Nocianitri, Komang Ayu; Hapsari, Ni Made Indri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 3 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i03.p10, 2019)
The aim of this study was to know the effect of adding soy protein isolate (ISP) to the characteristics of kamaboko barramundi fish (Lates calcalifer) and to know the right addition of ISP that can produce kamaboko with the best characteristics. The study used a completely randomized design with the addition treatment of ISP that consis ts of 5 levels: 0%, 4%, 8%, 12%, and 16%. The treatment was repeated 3 times to obtain 15 experimental units. The data w as analyzed by variance and if it influential to the variable then continued with the Duncan test. The results showed that the addition of ISP on the producing of kamaboko had a highly significant effect to texture (gel strength), moisture content, protein content, ash content, hedonic test (color, texture, taste, overall acceptance) and scoring test (folding test and bite test). The addition of 12% ISP produced kamaboko with the best characteristics with gel strength 1404.76 gf/cm 2 , water content 74.42%, protein content 15.40%, fat content 3.64%, ash content 3.55%, color , texture, taste, and overall acceptances were like d , aroma rather like d , appearance of meat without fiber and without foreign things , folding test does not crack if folded 4 times , and bite test rather strong specific product elasticity. Keywords : soy protein isolate, barramundi fish, kamaboko, characteristics